PERAN BUDAYA LOKAL TERHADAP PERKEMBANGAN PARIWISATA JIKO MALAMO - Asnita Ode Samili; Syarifuddin Adjam; Jainudin Hasim (Universitas Khairun, 2023)
This research was conducted at the Jiko Malamo tourism site in the Takome sub-district. The objectives of this research include: (1) knowing the role of local culture in tourism development, and (2) describing the impact of local culture on tourism development. The research was conducted in a qualitative form with descriptive analysis. The results showed that the role of local culture in jiko malamo tourism can be seen from changes in several existing cultural elements, including the development of local community knowledge systems, emergence of new livelihoods, recognition of language diversity, technological advances, formation of social organizations, emergence of commercialization of hospitality, shifts solidarity values, as well as the emergence of horizontal conflicts between local communities. The tourism management strategy in Takome Village still leads to the type of cooperative solidarity, while the pattern of community relations is in accordance with the characteristics of the community which is marked by a strong culture of mutual cooperation, consensus in decision making, and life that still has a traditional rural nuance.